A Linguistic Explanation of Information - Leiming Shi (Proceedings, 2022)
We can tentatively extend the idea of semiotics and linguistics to consider that matter itself is its own symbol, which is also its own language. Matter itself has a symbol and a meaning. Matter is a noun and a verb at once. The entire world is a language. Information is a state where language is not understood or where it is prior to being interpreted. Once it is interpreted or understood, it is a language. At this level, we can find that, in fact, the information is a specific form of language and is a subset of language, and not the opposite.